Impact of the 2014 American Academy of Pediatrics Immunoprophylaxis Policy on the Rate, Severity, and Cost of Respiratory Syncytial Virus Hospitalizations among Preterm Infants - Krilov, Leonard R.; Fergie, Jaime; Goldstein, Mitchell; Brannman, Lance (American Journal of Perinatology, 2020)
Objective This study examined the rate, severity, and cost of respiratory syncytial virus (RSV) hospitalizations among preterm infants 29 to 34 weeks gestational age (wGA) versus term infants before and after a 2014 change in the American Academy of Pediatrics policy for RSV immunoprophylaxis.Study Design Preterm (29–34 wGA) and term infants born from July 2011 to March 2017 and aged < 6 months were identified in a U.S. commercial administrative claims database. RSV hospitalization (RSVH) rate ratios, severity, and costs were evaluated for the 2011 to 2014 and 2014 to 2017 RSV seasons. Postpolicy changes in RSVH risks for preterm versus term infants were assessed with difference-in-difference (DID) modeling to control for patient characteristics and temporal trends.Results In the DID analysis, prematurity-associated RSVH risk was 55% greater in 2014 to 2017 versus 2011 to 2014 (relative risk = 1.55, 95% confidence interval: 1.10–2.17, p = 0.011). RSVH severity increased among preterm infants after 2014 and was highest among those aged < 3 months. Differences in mean RSVH costs for preterm infants in 2014 to 2017 versus 2011 to 2014 were not statistically significant.Conclusion RSVH risk for preterm versus term infants increased after the policy change, confirming previous national analyses. RSVHs after the policy change were more severe, particularly among younger preterm infants.
Keywords: gestational age; hospitalization; immunization, passive; infant; infant, premature; observational study; practice guideline as topic; respiratory syncytial viruses